Kajian Place Dependence Warisan Budaya Wujud pada Sumbu Filosofi di Kota Yogyakarta - Pawitra Sari; Aris Munandar; Indung Sitti Fatimah (Jurnal Lanskap Indonesia, 2019)
Yogyakarta City has a privilege in the history of the Mataram Kingdom relics either tangible or intangible. One of them is the philosophy axis. The philosophy axis is manifested in the form of a path that has historical objects as the elements of forming a city. The main elements are Tugu Yogyakarta, Malioboro Street, Zero Kilometer, and South Square is now being used in the open space of the city. The aims of this study were to examine the place dependence on the four historical objects with the respondents. The study has already done using qualitative and quantitative methods. The main of qualitative methods by distribution questionnaires involve the perception of natives, newcomers, and tourists as much as 327 respondents. Other qualitative methods were done by using a descriptive approach to the literature review and interviews, as well as field observation. Quantitative methods by using a non-parametric of different test with Mann-Whitney U for testing of perception between two samples. The results of this study, perception between the natives and newcomers was no difference. The results showed that place dependence obtained the doubtful value of 83.33%, the disagree value of 8.33% and the agreed value of 8.33%. The importance of place dependence as a recommendation in planning is the preservation of tangible cultural heritage and increasing the dimensions of place attachment in public space, especially the Zero Kilometer which has the weakest value. Finally, Yogyakarta City would be realized by UNESCO as one of World Heritage City about cultural heritage. Keywords: historical objects, perception, place dependence, public space, tangible cultural heritage Diterima